Pencil lead and manufacturing method thereof
By using clay, coloring materials and alkali metal elements of specific properties in the pencil core, combined with the firing process of alkali metal hydroxide aqueous solution, the problem of insufficient strength and hygroscopic resistance of the pencil core is solved, and a pencil core manufacturing with high strength, good erasability and low energy consumption is achieved.
Patent Information
- Application Number
- CN202380047457.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-24
- Filing Date
- 2023-06-19
- Publication Date
- 2025-02-28
AI Technical Summary
The existing pencil cores have shortcomings in strength and hygroscopic resistance, especially the writing strength and hygroscopic deterioration problems caused by hygroscopic when the tip is sharp, and the high-temperature firing technology consumes high energy.
By containing clays of specific physical properties, coloring materials and alkali metal elements, a specific peak characteristic clay measured by XRD is mixed and sintered in combination with an aqueous alkali metal hydroxide solution to form a pencil core with high strength and good erasability.
It achieves that even the tip has sufficient writing strength, reduces deterioration caused by hygroscopy, and has erasability, suitable for automatic pencil use, while avoiding high energy consumption of high-temperature firing technology.
Smart Images

Figure CN119546711A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a pencil lead which has sufficient strength for writing even when the tip is sharpened, has little deterioration due to moisture absorption, and has erasability, and a method for producing the same. Background Art
[0002] Conventionally, as unfired pencil leads, for example, the following are known:
[0003] 1) A colored pencil lead, wherein, in a non-sintered colored pencil lead using at least a binder, a base material, a lubricant, and a coloring material, talc having an average particle size of 10 to 30 μm produced by a wet pulverization method is used as the base material (see, for example, Patent Document 1); A colored pencil lead, wherein a porous calcium carbonate fiber is used as at least a part of the base material (see, for example, Patent Document 2);
[0004] 2) A colored pencil lead, characterized in that the pencil lead contains a resin in which a dye is dissolved or encapsulated, and the pencil lead is a fired ceramic core obtained by mixing at least boron nitride and a ceramic binder and firing; a colored pencil lead is an unfired ceramic core obtained by mixing at least a ceramic binder and molding (for example, see Patent Document 3);
[0005] 3) A pencil lead characterized in that, in a polymer-based, extrudable, non-expanded, non-sintered graphite-containing pencil lead, 25-100%, preferably 50-100%, of the total weight of the graphite is formed by expanded graphite; A pencil lead comprising: 40-60%, preferably 44-50% by weight of graphite, 15-40%, preferably 20-35% by weight of a polymer, 5-15%, preferably 6-10% by weight of a colorless or white mineral filler, 5-20%, preferably 5-15% by weight of carbon black, in particular carbon black obtained by coating or mixing polyolefins or polyolefin waxes, 0-16%, preferably 5-15% by weight of additives (see, for example, Patent Document 4), etc.
[0006] However, the current status of the pencil leads of Patent Documents 1, 2 and 4 is that the strength is not yet sufficient, or there are problems such as deterioration due to moisture absorption. The colored pencil lead of Patent Document 3 is excellent in erasability without sacrificing strength, but further strength is required, especially further improvement in strength to achieve sufficient writing even when the tip is sharpened, and further improvement in moisture absorption resistance. If the lead is manufactured by high-temperature firing in this way, a lead with no problems in strength can be manufactured, but it is necessary to set the firing furnace to 800°C or more, preferably to 1000°C or more, which is a big problem in terms of energy.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application Laid-Open No. 9-12960 (claims, examples, etc.)
[0010] Patent Document 2: Japanese Patent Application Laid-Open No. 9-176553 (claims, examples, etc.)
[0011] Patent Document 3: Japanese Patent Application Laid-Open No. 2015-160887 (claims, examples, etc.)
[0012] Patent Document 4: Japanese Patent Application Publication No. 2008-935 (claims, examples, etc.) Summary of the invention
[0013] Problem that the invention aims to solve
[0014] The present disclosure is made in view of the above-mentioned problems and current situations of the prior art and aims to solve them, and its purpose is to provide a pencil lead which has sufficient strength for writing even when the tip is sharpened, has little deterioration due to moisture absorption, and has erasability, and a method for manufacturing the same. Another purpose is to provide a pencil lead which can be manufactured without using a firing furnace at a high temperature exceeding 500° C. and a method for manufacturing the same.
[0015] Solutions for solving problems
[0016] The inventors of the present invention have conducted intensive studies in view of the above-mentioned conventional problems and have found that the above-mentioned target pencil lead and the method for producing the same can be obtained by containing at least clay, a coloring material and an alkali metal element having specific physical properties, and have thus completed the present disclosure.
[0017] That is, the pencil lead of the present disclosure is characterized in that it contains at least: clay whose 2θ peak appears at 12.4±0.5 and / or 24.5±1.0 in the measurement based on XRD; a coloring material; and an alkali metal element. In addition, it is characterized in that it contains at least: clay, a coloring material and an alkali metal element, and the 2θ peak of the pencil lead appears at 12.4±0.5 and / or 24.5±1.0 in the measurement based on XRD.
[0018] Preferably, the aforementioned coloring material is selected from carbon particles.
[0019] It is preferred that the alkali metal element be selected from sodium or potassium.
[0020] The method for producing a pencil lead disclosed herein is characterized in that clay is dried at 50°C to 500°C so that a 2θ peak appears at 12.4±0.5 and / or 24.5±1.0 in XRD measurement, the dried clay is mixed with a coloring material and an alkali metal hydroxide aqueous solution, the mixture is molded, and then calcined at 50°C to 500°C.
[0021] Preferably, the aforementioned coloring material is selected from carbon particles.
[0022] Preferably, the alkali metal hydroxide aqueous solution is selected from sodium hydroxide or potassium hydroxide.
[0023] In addition, in this specification (including the Examples etc. mentioned later), "XRD" is an abbreviation of X-ray diffraction (X-ray diffraction), and specifically, it is a value measured by MiniFlex (made by Rigaku Corporation).
[0024] Effects of the Invention
[0025] According to the present disclosure, there are provided a pencil lead suitable for mechanical pencils, pencils, etc., which has sufficient strength for writing even when the tip is sharpened, is less deteriorated by moisture absorption, and has erasability, and a method for producing the same.
[0026] The objects and effects of the present disclosure are realized and achieved particularly by using the constituent elements and combinations pointed out in the claims.Both the above general description and the detailed description to be given below are exemplary and explanatory and do not limit the present disclosure described in the claims. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The following are XRD spectra of the clay (halloysite) used in Examples 1 to 5 and Comparative Examples 1 and 2.
[0028] Figure 2 It is the XRD spectrum of the clay (halloysite) used in Examples 6 to 10 and Comparative Example 3.
[0029] Figure 3 It is the XRD spectrum of the clay (halloysite) used in Examples 11 to 15 and Comparative Examples 4 and 5.
[0030] Figure 4 It is the XRD spectrum of the clay (halloysite) used in Examples 16 to 20 and Comparative Example 6.
[0031] Figure 5 This is the XRD spectrum of the clay (dickite) used in Examples 21 and 22.
[0032] Figure 6These are XRD spectra of the clay (dickite) used in Example 23 and Comparative Example 7.
[0033] Figure 7 This is the XRD spectrum of the clay (kaolinite) used in Examples 24 and 25.
[0034] Figure 8 These are XRD spectra of the clay (kaolinite) used in Example 26 and Comparative Example 8.
[0035] Fig. 9 This is an XRD pattern of the clay in the pencil lead produced using untreated clay in Example 27.
[0036] Fig.10 This is an explanatory diagram for explaining the test method of tip strength (initial). DETAILED DESCRIPTION
[0037] The following is a detailed description of the embodiments of the present disclosure. However, the scope of protection of the present disclosure is not limited to the embodiments described in detail below, and it should be noted that it involves the inventions and their equivalents recorded in the claims. In addition, the present disclosure can be implemented based on the contents disclosed in this specification and the technical common sense in the field (including conventional technical selections and obvious features).
[0038] The pencil lead of the present disclosure is as follows: in the first disclosure, it is characterized in that it contains at least: clay whose 2θ peak appears at 12.4±0.5 and / or 24.5±1.0 in the measurement based on XRD; a coloring material; and an alkali metal element. In addition, in the second disclosure, it is characterized in that it contains at least: clay, a coloring material and an alkali metal element, and the peak of 2θ of the pencil lead appears at 12.4±0.5 and / or 24.5±1.0 in the measurement based on XRD.
[0039] Hereinafter, the present disclosure includes both the first disclosure and the second disclosure.
[0040] <clay>
[0041] In the first disclosure, the clay used is one having a 2θ peak at 12.4±0.5 and / or 24.5±1.0 in measurement by XRD (X-ray diffraction: XRD).
[0042] In the first disclosure, when using clay whose 2θ peak appears at 12.4±0.5 and / or 24.5±1.0 in XRD measurement, by using clay with such characteristics, the effect of the present disclosure can be exerted, that is, the clay surface of the clay having such characteristic values is activated, and the alkali metal elements contained therein become a condensation polymer and solidify to form a core. In addition, this is because a high-strength porous core can be formed without heating at an extremely high temperature of more than 1000°C as in the conventional calcination of the core.
[0043] As the clay that can be used, for example, at least one of halloysite, dickite, industrial kaolin, clay, sodium aluminosilicate, potassium aluminosilicate, calcium aluminosilicate, beidellite, magnesia iron ore, kaolinite, halloysite, montmorillonite, bentonite, etc. (each alone or as a mixture of two or more, and the same applies to the following). Among these clays, those having the above-mentioned characteristic values in the 2θ peak in the above-mentioned XRD measurement are further used.
[0044] Among the above-mentioned various clays, those having the above-mentioned characteristic values can be used as they are. In addition, when the various clays do not have the above-mentioned characteristic values, the various clays can be dried at 50° C. to 500° C., preferably at 80° C. to 500° C., and further treated with appropriate force to obtain clays having the above-mentioned characteristic values. In particular, it is desirable to obtain clays having the above-mentioned characteristic values by drying the various clays at 80° C. to 500° C. to further exert the effects of the present disclosure, production efficiency, and environmental load.
[0045] The content of the clay having this characteristic value is preferably 10 to 70% by mass, more preferably 20 to 60% by mass, relative to the total amount of the pencil lead. When the content of the clay having this characteristic value is 10% by mass or more, a breakage strength similar to that of a conventional sintered porous core body and having no practical problems can be obtained, and when it is 70% by mass or less, a pencil lead having a smooth writing condition and a high-density line can be obtained.
[0046] 〈Coloring Materials〉
[0047] In the present disclosure, the coloring material used is a substance used for coloring a pencil lead into a colored lead, and various pigments (such as inorganic pigments, organic pigments, fluorescent pigments, microcapsule pigments), dyes (such as oil-soluble dyes, salt-forming dyes), etc. can be used.
[0048] As coloring materials that can be preferably used, for example, there can be mentioned at least one of graphite, carbon black (furnace black, channel black, acetylene black, thermal black), carbon nanotubes, carbon nanofibers, fullerenes, titanium oxide, zinc oxide, iron oxide pigments, Prussian blue, Prussian blue, aluminum oxide, barium sulfate, calcium carbonate, chromium oxide, manganese violet, ultramarine blue, chromium hydrate, ferric blue and other inorganic pigments, disazo yellow AAA, pyrazolone orange and other azo organic pigments, phthalocyanine blue, phthalocyanine green and other cyanine organic pigments, quinacridone red and other high-grade organic pigments, organic pigments, fluorescent pigments, microcapsule pigments, mica titanium, iron oxide-coated mica titanium, iron oxide-coated mica titanium, microparticles of titanium oxide coated mica titanium, microparticles of zinc oxide coated mica titanium, iron oxide coated mica titanium, barium sulfate coated mica titanium, glass flakes containing titanium oxide, and bright pigments such as silicon dioxide containing zinc oxide.
[0049] Particularly preferably, from the perspective of weather resistance and heat resistance, it is preferred to use those selected from carbon particles, namely graphite, carbon black (furnace black, channel black, acetylene black, thermal black), carbon nanotubes, carbon nanofibers, fullerenes; and those selected from inorganic pigments, namely titanium oxide, iron oxide pigments, etc.
[0050] The content of these coloring materials is preferably 30 to 90% by mass, more preferably 40 to 80% by mass, based on the total amount of the pencil lead.
[0051] When the content of the coloring material is 30% by mass or more, the color development of the line can be improved, and when the content is 90% by mass or less, the strength during writing can be improved.
[0052] 〈Alkali metal elements〉
[0053] In the present disclosure, the alkali metal element (Li to Fr) used is used for the polycondensation reaction of the clay mineral, and preferably, from the viewpoint of reactivity, the alkali metal element is preferably selected from sodium or potassium.
[0054] In the present disclosure, from the perspective of reactivity, any form of pencil lead containing sodium or potassium may be used, for example, it may be used in the form of sodium hydroxide (NaOH), potassium hydroxide (KOH), sodium silicate (Na2SiO3), potassium silicate (K2SiO3), etc., which are alkali metal hydroxides.
[0055] The content of these alkali metal elements (Na, K, etc.) is preferably 3% by mass or more, more preferably 3 to 60% by mass, based on the total amount of the pencil lead in terms of the amount of the alkali metal element.
[0056] By setting the content of the alkali metal element to 3% by mass or more, a core having a breakage strength that is not a problem in practical use can be formed through the above-mentioned reaction. On the other hand, by setting it to 60% by mass or less, a porous core having suitable continuous pores that are not too dense can be formed.
[0057] The first disclosure is characterized in that it contains at least: clay whose 2θ peak appears at 12.4±0.5 and / or 24.5±1.0 in the above-mentioned XRD measurement; a coloring material; and an alkali metal element. In addition, a prescribed amount of alkali metal salt, alkaline earth metal salt, aluminum salt, etc. can be appropriately contained within a range that does not impair the effects of the present disclosure.
[0058] In addition, the pores of the obtained pencil lead may be further filled with lubricating oil.
[0059] Examples of the lubricating oil used include paraffin oil, α-olefin oil, fatty acid ester, ester oil such as alkylene glycol ether, synthetic oil such as silicone oil, vegetable oil such as castor oil, and grease.
[0060] The pencil lead disclosed in the first disclosure can be produced, for example, by mixing various clays whose 2θ peaks appear at 12.4±0.5 and / or 24.5±1.0 in XRD measurement with the above-mentioned coloring material and the above-mentioned alkali metal hydroxide aqueous solution, molding the mixture into a predetermined shape / size, and then calcining the mixture at 50°C to 500°C, preferably 50°C to 300°C, using an electric furnace, microwave heating, vacuum heating furnace, etc. Preferably, the pencil lead can be produced by drying at least clay at 80°C to 500°C, preferably 80°C to 300°C, so that the 2θ peaks appear near the above-mentioned predetermined values in XRD measurement, mixing the dried clay, the above-mentioned coloring material and the above-mentioned alkali metal hydroxide aqueous solution in predetermined amounts, molding the mixture into a predetermined shape / size, and then calcining the mixture at 50°C to 500°C, preferably 50°C to 300°C, using the above-mentioned various heating means, etc.
[0061] The pencil lead disclosed in the first disclosure uses clay having a 2θ peak at 12.4±0.5 and / or 24.5±1.0 in XRD measurement, and specifically combines it with an alkali metal element in addition to the coloring material contained therein, thereby improving the strength through a reaction that produces a geopolymer, i.e., geopolymerization. In particular, a pencil lead having sufficient strength for writing even when the tip is sharpened, little deterioration due to moisture absorption, and good erasability is obtained.
[0062] Next, the pencil lead disclosed in claim 2 is characterized by comprising at least clay, a coloring material and an alkali metal element, wherein the 2θ peak of the pencil lead appears at 12.4±0.5 and / or 24.5±1.0 in XRD measurement.
[0063] The pencil lead of the second disclosure contains at least the clay, the coloring material and the alkali metal element in predetermined amounts, and the effect of the present disclosure can be exerted as long as the 2θ peak of the obtained pencil lead appears at 12.4±0.5 and / or 24.5±1.0 in XRD measurement.
[0064] In the second disclosure, the clay, coloring material, alkali metal element, and other components used are the same as those in the first disclosure, and therefore, description thereof will be omitted.
[0065] The pencil lead of the second disclosure uses the untreated clay of the first disclosure instead of using clay having the above-mentioned characteristic values as in the first disclosure, and comprises the untreated clay, a coloring material and each component of an alkali metal element. Therefore, in the pencil lead obtained by sintering in a suitable temperature range of 50°C to 500°C according to the production method of the first disclosure, if the peak of 2θ in the clay of the pencil lead by XRD measurement appears at 12.4±0.5 and / or 24.5±1.0, the above-mentioned geopolymerization reaction occurs, the constituent components are bonded to each other, and a high-strength core body is formed as a whole, and the effect of the present disclosure can be exerted in the same manner as in the first disclosure.
[0066] The pencil lead of the second disclosure exhibits the effects of the present disclosure in the same manner as the pencil lead of the first disclosure. The entire lead is made of a geopolymer, thereby improving strength. In particular, a pencil lead is obtained which has sufficient strength for writing even when the tip is sharpened, has little deterioration due to moisture absorption, and has erasability.
[0067] The pencil lead and the method for producing the same disclosed in the present invention are not limited to the above-described embodiment, and can be implemented with various modifications within the scope of the technical concept of the present invention.
[0068] For example, geopolymerization reactions tend to advance at high temperatures, and are generally accelerated by heating in industry (calcination process). However, if a long time is acceptable, the process may be performed without accelerating the reaction by heating.
[0069] In addition, when the surfaces of the clay particles are sufficiently exposed and activated in the drying step, this step is omitted.
[0070] Examples and Comparative Examples
[0071] Next, the pencil lead of the present disclosure will be described in more detail based on each of Examples and Comparative Examples, but the present disclosure is not limited to the following Examples and the like.
[0072] (Examples 1 to 5, Comparative Examples 1 and 2)
[0073] Clay: Halloysite-7A 30 mass%
[0074] Coloring material: 50% by mass of flake graphite (CSP, manufactured by Nippon Graphite Industries, Co., Ltd.)
[0075] Alkali metal: potassium hydroxide (50% aqueous solution) 20% by mass
[0076] The clays used were those that were not calcined (RT: room temperature, the same below), calcined at 80°C, 120°C, 200°C, 300°C, 500°C, and 600°C. For each of the clays calcined at 80°C to 500°C, the Figure 1 The XRD spectrum of 2θ confirmed that the peak of 2θ in the XRD measurement was within the range of 12.5±0.5 and / or 24.5±1.0. Neither the above peaks were observed in the non-sintered sample of Comparative Example 1 nor the sample sintered at 600°C of Comparative Example 2.
[0077] The above-mentioned blended components were pelletized, and then formed into thin strands using a screw extruder, and dried at 50° C. for 24 hours to obtain pencil leads having a diameter of 2.5 mm and a length of 180 mm.
[0078] (Examples 6 to 10, Comparative Example 3)
[0079] Clay: Halloysite-7A 30 mass%
[0080] Coloring material: 50% by mass of flake graphite (CSP, manufactured by Nippon Graphite Industries, Co., Ltd.)
[0081] Alkali metal: sodium hydroxide (50% aqueous solution) 20% by mass
[0082] The clays used were those that were not calcined, calcined at 80°C, calcined at 120°C, calcined at 200°C, calcined at 300°C, and calcined at 500°C. For each of the clays calcined at 80°C to 300°C, the Figure 2 The XRD spectrum of 2θ was confirmed to be within the range of 12.5±0.5 and 24.5±1.0 in the XRD measurement. In the sample without calcination treatment of Comparative Example 3, none of the above peaks was observed.
[0083] The above-mentioned blended components were pelletized, molded into thin strands using a screw extruder, and dried at 50° C. for 24 hours to obtain pencil leads having a diameter of 2.5 mm and a length of 180 mm.
[0084] (Examples 11 to 15, Comparative Examples 4 and 5)
[0085] Clay: Halloysite-7A 30 mass%
[0086] Coloring material: 50% by mass of flake graphite (CSP, manufactured by Nippon Graphite Industries, Co., Ltd.)
[0087] Alkali metal: potassium silicate (50% aqueous solution) 20% by mass
[0088] The clays used were those that were not calcined, calcined at 80°C, 120°C, 200°C, 300°C, 500°C, and 1000°C. For each of the clays calcined at 80°C to 500°C, the Figure 3 The XRD spectrum of 2θ was confirmed to be within the range of 12.5±0.5 and 24.5±1.0 in the XRD measurement. Neither the above peaks were observed in the non-sintered sample of Comparative Example 4 nor in the sample sintered at 1000°C of Comparative Example 5.
[0089] The above-mentioned blended components were pelletized, and then formed into thin strands using a screw extruder, and dried at 50° C. for 24 hours to obtain pencil leads having a diameter of 2.5 mm and a length of 180 mm.
[0090] (Examples 16 to 20, Comparative Example 6)
[0091] Clay: Halloysite-7A 30 mass%
[0092] Coloring material: 50% by mass of flake graphite (CSP, manufactured by Nippon Graphite Industries, Co., Ltd.)
[0093] Alkali metal: sodium silicate (50% aqueous solution) 20% by mass
[0094] The clays used were those that were not calcined, calcined at 80°C, calcined at 120°C, calcined at 200°C, calcined at 300°C, and calcined at 500°C. For each of the clays calcined at 80°C to 300°C, the Figure 4The XRD spectrum of 2θ was confirmed to be within the range of 12.5±0.5 and 24.5±1.0 in the XRD measurement. In the sample without calcination treatment of Comparative Example 6, none of the above peaks was observed.
[0095] The above-mentioned blended components were pelletized, and then formed into thin strands using a screw extruder, and dried at 50° C. for 24 hours to obtain pencil leads having a diameter of 2.5 mm and a length of 180 mm.
[0096] (Examples 21 and 22)
[0097] Clay: Dickite (Dickite-2M1) 30 mass%
[0098] Coloring material: 50% by mass of flake graphite (CSP, manufactured by Nippon Graphite Industries, Co., Ltd.)
[0099] Alkali metal: potassium hydroxide (50% aqueous solution) 20% by mass
[0100] The clay used was calcined at 80°C and 120°C. The clays calcined at 80°C and 120°C were Figure 5 From the XRD spectrum, it was confirmed that the 2θ peaks in the XRD measurement were in the range of 12.5±0.5 and 24.5±1.0.
[0101] The above-mentioned blended components were pelletized, and then formed into thin strands using a screw extruder, and dried at 50° C. for 24 hours to obtain pencil leads having a diameter of 2.5 mm and a length of 180 mm.
[0102] (Example 23, Comparative Example 7)
[0103] Clay: Dickite (Dickite-2M1) 30 mass%
[0104] Coloring material: 50% by mass of flake graphite (CSP, manufactured by Nippon Graphite Industries, Co., Ltd.)
[0105] Alkali metal: sodium hydroxide (50% aqueous solution) 20% by mass
[0106] The clay used was calcined at 200°C and 600°C. For the clay calcined at 200°C, Figure 6 The XRD spectrum of 2θ was confirmed to be within the range of 12.5±0.5 and 24.5±1.0 in the XRD measurement. In the sample of Comparative Example 7 calcined at 600° C., none of the above peaks was observed.
[0107] The above-mentioned blended components were pelletized, and then formed into thin strands using a screw extruder, and dried at 50° C. for 24 hours to obtain pencil leads having a diameter of 2.5 mm and a length of 180 mm.
[0108] (Examples 24 and 25)
[0109] Clay: Industrial kaolinite (Kaolinite-1A, manufactured by BASF Corporation) 30% by mass
[0110] Coloring material: 50% by mass of flake graphite (CSP, manufactured by Nippon Graphite Industries, Co., Ltd.)
[0111] Alkali metal: sodium hydroxide (50% aqueous solution) 20% by mass
[0112] The clay used was calcined at 80°C and 120°C. The clays calcined at 80°C and 120°C were Figure 7 From the XRD spectrum, it was confirmed that the 2θ peaks in the XRD measurement were in the range of 12.5±0.5 and 24.5±1.0.
[0113] The above-mentioned blended components were pelletized, and then formed into thin strands using a screw extruder, and dried at 50° C. for 24 hours to obtain pencil leads having a diameter of 2.5 mm and a length of 180 mm.
[0114] (Example 26, Comparative Example 8)
[0115] Clay: Industrial kaolinite (Kaolinite-1A, manufactured by BASF Corporation) 30% by mass
[0116] Coloring material: 50% by mass of flake graphite (CSP, manufactured by Nippon Graphite Industries, Co., Ltd.)
[0117] Alkali metal: sodium silicate (50% aqueous solution) 20% by mass
[0118] The clay used was calcined at 200°C and calcined at 1000°C. For the clay calcined at 200°C, the Figure 8 The XRD spectrum of , confirmed that the 2θ peaks in the XRD measurement were within the range of 12.5±0.5 and 24.5±1.0. In the samples of Comparative Example 8 calcined at 1000°C, none of the above peaks was observed.
[0119] The above-mentioned blended components were pelletized, and then formed into thin strands using a screw extruder, and dried at 50° C. for 24 hours to obtain pencil leads having a diameter of 2.5 mm and a length of 180 mm.
[0120] (Example 27)
[0121] Clay: Halloysite-7A 30 mass%
[0122] Coloring material: 50% by mass of flake graphite (CSP, manufactured by Nippon Graphite Industries, Co., Ltd.)
[0123] Alkali metal: sodium hydroxide (50% aqueous solution) 20% by mass
[0124] The clay used was not calcined. The untreated clay was pelletized and then formed into thin wires in a screw extruder. After forming into a core, it was dried at 300°C for 24 hours to obtain a pencil lead with a diameter of 2.5 mm and a length of 180 mm. After that, the core of the sample was crushed and only the clay (halloysite) was extracted and subjected to XRD measurement. Fig. 9 The XRD spectrum of the core was confirmed to be within the range of 12.5±0.5 and 24.5±1.0 based on the 2θ peaks in the XRD measurement. As mentioned above, none of the above peaks were observed in the non-sintered core of Comparative Example 1 (no treatment was also performed during the manufacture of the core).
[0125] The pencil leads prepared in Examples 1 to 27 and Comparative Examples 1 to 8 were assembled into pencils in a conventional manner and used for the following tests.
[0126] (Reference example)
[0127] The tip strength test was conducted in the same manner as in the pencil leads of the Examples and Comparative Examples using HI-UNI 4B manufactured by Mitsubishi Pencil Co., Ltd. The result was 5.0N.
[0128] (Test method)
[0129] The pencils produced using the pencil leads of the Examples and Comparative Examples obtained above were evaluated for tip strength, water resistance, and writing properties by the following test methods. The evaluation results are shown in Tables 1 to 9 below.
[0130] [Test method for tip strength]
[0131] Ten pencil leads obtained in each of the above-mentioned embodiments and comparative examples were sharpened using a Mitsubishi Pencil Micro-Sharpener (trade name: Pocket Sharpner DPS-101PLT) under a normal temperature / normal humidity (23°C, 50%) environment and a high temperature / high humidity (35°C, 80%) environment. Fig.10 As shown, make the tip sharp and align the tip surface to A force gauge (manufactured by Imada Seisakusho Co., Ltd.) was used to apply stress at an angle of 60 degrees, and the maximum stress (unit: N) (initial strength) when the tip was broken was measured. The greater the stress, the better the tip strength.
[0132] [Test method for water resistance]
[0133] First, after measuring the initial bending strength of the pencil lead, each pencil lead was placed in water at 25°C and 65% humidity, and the bending strength of the pencil lead after being left for one week was measured. The bending strength D2 after immersion in water and the initial bending strength D1 were calculated using the following formula and compared with the values.
[0134] Water resistance = D2 / D1×100
[0135] (Writing evaluation test)
[0136] Each pencil lead of the above-mentioned examples and comparative examples was formed into pencils as described above, and ten reviewers were asked to write and fill in "Mitsubishi Pencil Co., Ltd." on 400-character manuscript paper, and compared with the pencil of the reference example, the evaluation was conducted according to the following evaluation criteria.
[0137] Evaluation criteria:
[0138] ○: 9 out of 10 people felt that the pencil was as good as or smoother than the reference pencil.
[0139] △: 3 to 8 out of 10 people felt that the writing resistance was greater than that of the reference pencil.
[0140] ×: 9 out of 10 people felt that the writing resistance was greater than that of the reference pencil.
[0141] [Table 1]
[0142] Comparative Example 1 Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 2 Sintering temperature(℃) RT 80 120 200 300 500 600 Tip strength (N) 2.8 5.9 6.3 6.7 6.4 6.8 6.8 Water resistance 105.6 97.0 92.1 94.7 96.6 106.1 106.1 Writing ○ ○ ○ ○ ○ △ ×
[0143] [Table 2]
[0144] Comparative Example 3 Example 6 Example 7 Example 8 Example 9 Example 10 Sintering temperature(℃) RT 80 120 200 300 500 Tip strength (N) 2.5 6.0 5.9 6.2 6.3 6.5 Water resistance 45.6 115.2 98.2 96.1 97.6 112.4 Writing ○ ○ ○ ○ ○ △
[0145] [Table 3]
[0146] Comparative Example 4 Embodiment 11 Example 12 Embodiment 13 Embodiment 14 Embodiment 15 Comparative Example 5 Sintering temperature(℃) RT 80 120 200 300 500 1000 Tip strength (N) 2.7 6.9 7.7 7.2 9.0 8.5 11.8 Water resistance 59.8 91.2 90.3 97.1 95.5 105.5 105.5 Writing ○ ○ ○ ○ ○ △ ×
[0147] [Table 4]
[0148] Comparative Example 6 Example 16 Embodiment 17 Embodiment 18 Embodiment 19 Embodiment 20 Sintering temperature(℃) RT 80 120 200 300 500 Tip strength (N) 3.4 9.6 10.8 10.7 10.9 10.5 Water resistance 60.0 86.7 92.2 91.8 98.7 100.4 Writing ○ ○ ○ ○ ○ △
[0149] [Table 5]
[0150] Embodiment 21 Embodiment 22 Sintering temperature(℃) 80 120 Tip strength (N) 5.6 6.6 Water resistance 101.5 100.0 Writing ○ ○
[0151] [Table 6]
[0152] Embodiment 23 Comparative Example 7 Sintering temperature(℃) 200 600 Tip strength (N) 7.1 8.6 Water resistance 93.6 100.0 Writing ○ ○
[0153] [Table 7]
[0154] Embodiment 24 Embodiment 25 Sintering temperature(℃) 80 120 Tip strength (N) 5.3 6.3 Water resistance 102.8 91.3 Writing ○ ○
[0155] [Table 8]
[0156] Embodiment 26 Comparative Example 8 Sintering temperature(℃) 200 1000 Tip strength (N) 9.8 9.7 Water resistance 92.1 92.0 Writing ○ ×
[0157] [Table 9]
[0158] Embodiment 27 Sintering temperature(℃) 300 Tip strength (N) 5.4 Water resistance 105.5 Writing ○
[0159] The results of Tables 1 to 9 clearly show that the pencil leads of Examples 1 to 27, which fall within the scope of the present disclosure (the first disclosure and the second disclosure), have sufficient strength when writing even when the tip is sharpened, have a tip strength, and are not inferior to conventional pencils in writing, and have no significant reduction in water resistance, compared to Comparative Examples 1 to 8, which are not within the scope of the present disclosure. In addition, as described above, pencil leads can be obtained that can be manufactured without applying a temperature exceeding 500° C. during manufacturing.
[0160] Furthermore, it was confirmed that the pencil leads of Examples 1 to 27, which fall within the scope of the present disclosure, also have good eraser erasability, similarly to the pencil lead of the reference example.
[0161] Industrial Applicability
[0162] A pencil lead suitable for mechanical pencils, pencils, etc., which has a low environmental load and does not involve a production process at a high temperature exceeding 500° C., is obtained.
Claims
1. A pencil lead, characterized in that: The invention at least comprises: clay having a 2θ peak at 12.4±0.5 and / or 24.5±1.0 in XRD measurement; a coloring material; and an alkali metal element.
2. The pencil lead according to claim 1, characterized in that The coloring material is selected from carbon particles.
3. The pencil lead according to claim 1 or 2, characterized in that: The alkali metal element is selected from sodium or potassium.
4. A pencil lead, characterized in that: The pencil lead at least comprises clay, a coloring material and an alkali metal element, wherein the 2θ peak of the pencil lead appears at 12.4±0.5 and / or 24.5±1.0 in the measurement based on XRD.
5. A method for manufacturing a pencil lead, characterized in that: The clay is dried at 50°C to 500°C so that the 2θ peak appears at 12.4±0.5 and / or 24.5±1.0 in XRD measurement, the dried clay is mixed with a coloring material and an alkali metal hydroxide aqueous solution, the mixture is molded, and then calcined at 50°C to 500°C.
6. The method for manufacturing a pencil lead according to claim 5, characterized in that: The coloring material is selected from carbon particles.
7. The method for manufacturing a pencil lead according to claim 5 or 6, characterized in that: The alkali metal hydroxide is selected from sodium hydroxide or potassium hydroxide.
Citation Information
Patent Citations
Colored pencil lead
JP1997012960A
Lead of colored pencil
JP1997176553A
Pencil
JP2008000935A
Colored pencil lead
JP2015160887A